PEMBELAJARAN IPS DALAM PERSPEKTIF KURIKULUM 2013 - Yoyo Supriono (Tatar Pasundan : Jurnal Diklat Keagamaan, 2018)
The curriculum is pretty basic guidelines in teaching and learning in education. Knowingly or not that the success or failure of an education, success or failure in achieving educational goals more or less dependent on the curriculum. Curriculum 2013 to develop learning experiences that provide opportunities for students to master the competencies required for the life of the present and the future. If the curriculum is designed well, systematic, comprehensive, and integral to all development and learning needs of learners to prepare themselves to face life in the future, then the expected goals would be realized. In reality the provision of education tend to cognitive, intellectual intelligence priority, and lack of education of character and personality. Key words: Study of Social Sciences, Learning,  In Curriculum 2013.